Lanthanide luminescence photophysical, analytical and biological aspects - Hänninen, Pekka; Härmä, Harri; Ala-Kleme, T.; SpringerLink (Online service). (Berlin New York Springer, 2011)
Lanthanides have fascinated scientists for more than two centuries now, and since efficient separation techniques were established roughly 50 years ago, they have increasingly found their way into industrial exploitation and our everyday lives. Numerous applications are based on their unique luminescent properties, which are highlighted in this volume. It presents established knowledge about the photophysical basics, relevant lanthanide probes or materials, and describes instrumentation-related aspects including chemical and physical sensors. The uses of lanthanides in bioanalysis and medicine are outlined, such as assays for in vitro diagnostics and research. All chapters were compiled by renowned scientists with a broad audience in mind, providing both beginners in the field and advanced researchers with comprehensive information on on the given subject.
Introduction; Photophysical basics of lanthanides; Lanthanide probes and materials; Luminescent stable chelates and macrocyclic compounds; Particulate labels; Chelating particles; Upconverters; NIR labels; Supramolecules and assemblies; Optical properties and applications of solid lanthanide materials; Lanthanide based chemical and physical sensors; Instrumental aspects on measuring lanthanide luminescence; Direct and time-resolved measurements; Frequency-domain measurements; Imaging systems; Bioanalytical and medical implications; Time-resolved and lifetime assays for in-vitro diagnostics and research; Electrochemiluminescence of lanthanides; Sensitized bioassays; Future of lanthanide luminescence and applications.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Rare earth metals -- Spectra; Luminescence; Rare earth metals -- Industrial applications; Lanthanoide; Electronic books